Karakteristik Nades (Natural Deep Eutectic Solvents) - Dewi, Yuli Piana; Zahrina, Ida; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
NADES (Natural Deep Eutectic Solvents) have been widely applied as a catalyst and solvents for extraction/reaction processes. The characteristics of NADES (pH, density, viscosity, surface tension, refractive index) are very important to application of NADES. The increasing density of NADES is influenced by the length of the carbon chain in the HBD and is influenced by the temperature where the higher the temperature the density will decrease. Viscosity is inversely proportional to temperature where the higher the temperature, the viscosity of NADES will decrease. NADES from choline chloride and glycerol are more polar than NADES from choline chloride and ethylene glycol. Surface tension increases with increasing salt ratio. As for the refractive index, the measurement of the refractive index decreases with increasing temperature.Keywords: Catalyst, Characteristics, Density, NADES, Viscosity.